Observation and numerical modeling of physical oceanography in the Balikpapan Bay, East Kalimantan: Preliminary results - Mutiara Rachmat Putri; Iwan P Anwar; Zetsaona Sihotang; Lamona I. Bernawis; Agus Setiawan; Muhammad Riza; Idris Mandang; Willem M. Tatipatta (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2021)
The Indonesian government plans to move the capital city from Jakarta to Penajam Paser Utara (PPU) which is the upstream area of Balikpapan Bay, East Kalimantan. There are several activities in the planned new capital city that potentially affect the condition of land and marine ecosystems, including clearing new land for housing and agriculture as well as expanding mining and petroleum areas. Directly or indirectly, these activities could affect the oceanographic conditions of Balikpapan Bay. For this reason, in order to obtain an up-to-date picture of Balikpapan Bay, an oceanographic survey was conducted in early March 2020. In addition, to support the analysis of marine dynamics in these waters and their predictions in the future, numerical simulations of hydrodynamic modeling were also carried out. Oceanographic observations indicate significant water stratification in the area about 20 km from the mouth of the bay. This result is also well illustrated in the hydrodynamic model numerical simulation, where there is a water loop at the confluence between salt and fresh water masses from two rivers 18-20 km from the mouth of Balikpapan Bay. Keywords:The national capital city of IndonesiaBalikpapan BayPhysical oceanography ObservationCoastal and marine Ecosystem